2005
DOI: 10.1093/ndt/gfh807
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of haemodialysis patients with malignancies and dose-adjusted chemotherapy

Abstract: Chemotherapy in patients with haemodialysis is feasible. Individual dose adjustment should be performed on the basis of pharmacokinetic data and the general condition of the patient, but it is still a matter of expert judgement, as there is no formal evidence available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…The contradiction in findings between these studies could be due to the small number of patients and lack of adjustment for several confounders that interfere with patient survival. Furthermore, there is evidence suggesting that MM patients on dialysis are variably undertreated and they do not receive all optimal chemotherapy for the fear of side effects, and usually they are not considered and they do not benefit from ASCT [10,16,17,20]. The ERA-EDTA Registry did not collect histological data, clinical or biochemical information and therefore cannot present results on the association between such possible prognostic factors and the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contradiction in findings between these studies could be due to the small number of patients and lack of adjustment for several confounders that interfere with patient survival. Furthermore, there is evidence suggesting that MM patients on dialysis are variably undertreated and they do not receive all optimal chemotherapy for the fear of side effects, and usually they are not considered and they do not benefit from ASCT [10,16,17,20]. The ERA-EDTA Registry did not collect histological data, clinical or biochemical information and therefore cannot present results on the association between such possible prognostic factors and the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are several smaller studies comparing outcome of patients with MM with renal insufficiency dependent on dialysis or not [14,16,[18][19][20]23]. In these reports, median survival on dialysis ranged from 2 months to 47 months, and this wide variation contains contradictory findings.…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacokinetic modeling study of chemotherapeutic agents used in patients with cancer undergoing dialysis suggested that these agents are generally overdosed. 30 Overdosing can aggravate systemic toxicities, with fatal consequences, whereas underdosing can lead to ineffective cancer treatment. Thus, because the CKD-ESRD population has a higher prevalence of cancer and the CKD-ESRD population is increasing, more precise dosing recommendations for this population are needed.…”
Section: Unique Features Of Nephrologic Disorders In Cancermentioning
confidence: 99%
“…There are many cytostatic drugs that are not dependent on kidney function. Cytostatic agents that are [ 10 ]. For dialysis patients the effect of dialysis has to be taken into account additionally.…”
Section: Hit Hard and Early In Infections And Tumor Therapymentioning
confidence: 99%